ANALISIS PENGARUH PEMASARAN LANGSUNG, KUALITAS PRODUK DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI SEMUA PRODUK YANG DITAWARKAN PADA LIVE STREAMING TIKTOK (STUDI LAPANGAN PADA MAHASISWA STIE BHAKTIPEMBANGUNAN ANGKATAN 2020) - Albiansyah, Albiansyah (Management Research and Business Journal, 2025)
This research aims to ind out whether Direct Marketing, Product Quality, and Online Customer Reviews on TikTok live streaming have an effect on Purchase Interest for all products offered. This type of research uses a quantitative approach, namely distributing questionnaires in the form of a Google form. The sampling technique used is purposive sampling which is included in nonprobability sampling. Purposive sampling is a technique for determining samples with certain considerations. Determining the number of samples in this study used a saturated sample with a population known through observation, and obtained 100 samples of active STIE Bhakti Pembangunan students class of 2020. Testing the hypothesis through the t test (partial) obtained the result that the Direct Marketing variable had a positive and signi icant effect on Purchase Interest with a calculated t value of 2.944 < t table 1.985 and a signi icance value of 0.004 > 0.05 and a correlation value of 0.881 meaning there is a positive relationship and the level of correlation very high. The Product Quality variable has a positive and signi icant effect on purchasing decisions with a calculated t value of 3.772 > t table 1.985 and a signi icance value of 0.000 > 0.05, as well as a correlation value of 0.926, meaning there is a positive relationship and the correlation level is very high. Online Customer Reviews have a positive and signi icant effect on purchasing decisions with a calculated t value of 6.558 > t table 1.985 and a signi icance value of 0.000 < 0.05 and a correlation value of 0.936, meaning there is a positive relationship and moderate correlation. The results of the F test (Simultaneous) in this research obtained F count 342.796 > F table 2.70 and a signi icance of 0.000 < 0.05, so simultaneously Direct Marketing, Product Quality and Online Customer Reviews in luence Purchase Interest, as well as the results of the analysis The coef icient of determination is 0.912, which means that 91.2% of interest in purchasing all products offered can be in luenced by the variables Direct Marketing, Product Quality and Online Customer Reviews, while the remainder is 8.8% is in luenced by other variables outside this research.